Anaerobic membrane bio‐reactors for waste activated sludge digestion: Tubular versus hollow fiber membrane configurations. Issue 3 (23rd July 2012) - Dagnew, M.; Pickel, J.; Parker, W.; Seto, P.
<x xml:space="preserve">Abstract</x> This article presents the results of pilot scale studies that examined the use of negative and neutral charged tubular and hollow fiber (HF) anaerobic membrane bio‐reactors (AnMBR) for anaerobic digestion of waste activated sludge. Both AnMBR configurations were operated at a hydraulic retention time of 15 days, a sludge retention time (SRT) of 30 days, and a total solids loading of 1.2–1.3 kg m−3 day−1. The results indicate that both membrane digesters showed comparable total chemical oxygen demand and volatile solids removals of 47.6 and 49.1% respectively while maintaining a throughput that was two times that of the completely stirred tank reactor (CSTR) type digesters. The performance of the AnMBRs was similar to that of CSTRs operating at 30 days SRT. The AnMBRs were operated for 160 days. During this period no significant fouling was observed and membrane cleaning was not required. The average fluxes for the neutral and negative tubular membranes were 32 and 39 LMH when operated at a trans‐membrane pressure TMP of 30 kPa. The HF membranes were operated at a constant flux of 11 LMH and the average TMP was less than 10 kPa. The critical flux measured for the tubular and HF membranes were near to 30 and 18 LMH mark respectively indicating a better performance by the former. However both AnMBR configurations generated comparable net energy. © 2012 American Institute of Chemical Engineers Environ Prog, 32: 598–604, 2013